2019
DOI: 10.3390/medicina55050123
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and Routine Complete Blood Count Components in HELLP Syndrome: A Matched Case Control Study

Abstract: Background and objective: Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are new readily available inflammatory markers that have been analyzed in pregnancy-induced hypertensive disorders such as preeclampsia. Studies on the NLR/PLR ratio in hemolysis, elevated liver enzymes, low-platelet count (HELLP) syndrome are limited in the current literature. We compared NLR/PLR and other complete blood count (CBC) components between women with HELLP syndrome and women with healthy pregnanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…In a study from Halim et al it was reported that liver tissue from HELLP patients was infiltrated with neutrophils in comparison to controls and liver tissue samples from acute fatty liver syndrome patients (35). Another study reported that neutrophils-to-lymphocyte ratio was higher in patients with HELLP syndrome majorly due to increased neutrophils in peripheral blood samples (13). This implicates that in HELLP patients, neutrophil counts are likely increased in the liver and in the peripheral circulation.…”
Section: Neutrophils Are Mediators Of Liver and Endothelial Damage Inmentioning
confidence: 95%
See 1 more Smart Citation
“…In a study from Halim et al it was reported that liver tissue from HELLP patients was infiltrated with neutrophils in comparison to controls and liver tissue samples from acute fatty liver syndrome patients (35). Another study reported that neutrophils-to-lymphocyte ratio was higher in patients with HELLP syndrome majorly due to increased neutrophils in peripheral blood samples (13). This implicates that in HELLP patients, neutrophil counts are likely increased in the liver and in the peripheral circulation.…”
Section: Neutrophils Are Mediators Of Liver and Endothelial Damage Inmentioning
confidence: 95%
“…With the Mississippi Triple Class System further categorization of the disease is done based on the severity of thrombocytopenia (7,8). Although traditionally HELLP syndrome was considered to be a severe form of preeclampsia (a disorder characterized by development of hypertension and proteinuria in pregnancy), several research lines are counteracting to this notion mainly because HELLP is associated with hypertension and/or proteinuria only in 80% of the cases and shows different cytokine activation and aggravated placental vascular lesions (9)(10)(11)(12)(13)(14)(15). Furthermore, the etiopathogenesis of this syndrome is complex and still not completely understood thus, additional and more specific/sensitive laboratory criteria are needed for up-to-date HELLP screening, diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that routine complete blood count (CBC) components, neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR) could be used as novel markers of systemic inflammatory response in various medical conditions, including pregnancy complications, [19][20][21][22][23][24][25][26][27][28][29] cancers, 30,31 cerebral hemorrhage, 32,33 ischemic stroke, [34][35][36] major cardiac events, 37,38 sepsis and infectious pathologies 39,40 and other diseases, in which these inexpensive and readily available inflammatory markers can help to stratify patient risks and individualize treatment strategy during everyday clinical practice. In particular, increasing evidence indicates that these inflammatory markers, such as NLR, MLR and neutrophil count, may be useful in predicting the risk of developing preeclampsia and invasion of gestational trophoblastic disease, and diagnosing HELLP syndrome, gestational diabetes mellitus, intrahepatic cholestasis of pregnancy, as well as hyperemesis gravidarum.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, increasing evidence indicates that these inflammatory markers, such as NLR, MLR and neutrophil count, may be useful in predicting the risk of developing preeclampsia and invasion of gestational trophoblastic disease, and diagnosing HELLP syndrome, gestational diabetes mellitus, intrahepatic cholestasis of pregnancy, as well as hyperemesis gravidarum. [19][20][21][22][23][24][25][26][27][28][29] Recently, it was found that raised NLR in early second trimester of pregnancy as predictors for development and severity of preeclampsia. 21 Wang et al also reported that NLR and MLR have better diagnostic accuracy in distinguishing preeclampsia from controls, suggesting they are effective indicators of clinical assessment, disease severity evaluation, and prognosis evaluation of preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation